Exploración Histórica de los Números y su Relación en la Contabilidad del Pueblo Nasa en Tiempos de la Unión de la Estrella con el Agua (2023)
This research aims to show and develop a reflection on the importance of exploring accounting issues, ethnohistory in the hieroglyphics of the Nasa Indigenous community from the time of the union of the star with water, for history in the singing profession. , is of importance and nature for this research in order to publicize a large part of the Nasa Indigenous culture of the Department of Cauca.